Family Psychology: Family Relationships and Their Impact on Personality Development - Xolboev Asqarali Mirxoldorovich (Peerian Journals Publishing, 2025)
This article studies the impact of family relationships on personality development. The importance of family relationships, parent-child relationships, and the family environment in the social, emotional, and psychological development of a person is analyzed. The article also considers factors affecting the quality of family relationships
Keywords: Family psychology; family relationships; personality development